2007
DOI: 10.1590/s0103-97332007000400031
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino signals from galactic binaries

Abstract: We analyze the possible origin of high-energy neutrinos coming from galactic sources. A model is proposed for neutrino hadroproduction in binary systems. Our results show that neutrino observatories like IceCube can establish whether TeV neutrinos and gamma rays emitted by microquasars are the decay products of pions. Such pions can be produced where the jet collides with the stellar wind of the companion star giving rise to hadronic interactions. We improve previous predictions by considering energy dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The spectral features should be detectable by an instrument like MAGIC and GLAST. Charged pion decay also leads to neutrino production as discussed in another work of the present meeting [1] (see also [27]). …”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The spectral features should be detectable by an instrument like MAGIC and GLAST. Charged pion decay also leads to neutrino production as discussed in another work of the present meeting [1] (see also [27]). …”
Section: Discussionmentioning
confidence: 63%
“…For the energy dependent pion multiplicity we will follow the prescription adopted by Mannheim and Schlickeiser (1994) [21] ξ π (E p /GeV − 1.22) 1/4 , which should be valid up to 10 4 GeV, and adopt a softer root growing law for higher energies (see Christiansen et al (2006b) for details [27]). Under these assumptions, it can be shown that the maximum proton energy produced amounts to more than 50 PeV at periastron and lies below 15 PeV near apastron [1,27]. It can be derived from the simple argument that the Larmor radius of the particle should be smaller than the size of the acceleration region [22,23].…”
Section: Gamma Ray Luminosity and Opacitymentioning
confidence: 99%
See 1 more Smart Citation